Democratize the Government of the University - Wong Cabanillas, Francisco Javier (2011)
Peru and irs universiries rcquite changes to conform (Osocial requirernenrs. Changos or reforrns, rhe importan¡ thing is how ro carry thcm OUt. plus, you start with what we can engage. The basic rherne is che govcrnrnenr of rhe universiry and also involving irs playcrs. Yesrerday was defincd thei restares: teachers, adrninisrrarors and srudents. Today should indudc represen tarivcs of (he social comrnuniry, from public and privare, mm as economic and polirical, In surnmary citizenship delined in direct relation ro rheir acadernic accions, and certainly diffil.'UlttO ser limits. 'Ihcrefore, proposals should not be excluded, orherwisc nor arrive at rhc desired success. This arricle is pare of rhe research ro propose a neccssary reform of rhc univcrsiry,